Application of response surface methodology for optimization of waterless biodiesel production from crude palm oil - คำธิตา, พัชรี; หะวะนิช, ศศิธร (Progress in Applied Science and Technology, 2017)
The purpose of this research was to apply the response surface methodology (RSM) based on Box Behnken design for the determination of optimum conditions on waterless biodiesel production from crude palm oil. The reaction process using acetone as co-solvent for the transesterification of palm oils in the presence of potassium hydroxide (KOH) catalyst has been developed. The relationship between the biodiesel yield as response and three operating parameters; the amount of acetone, KOH catalyst concentration and reaction temperature were analyzed by the second order regression equation. It was found that the RSM was successfully applied to analyze the interaction effects between the amount of acetone co-solvent and the reaction temperature on biodiesel yield. The optimum conditions were: 14 %wt acetone co-solvent, 1.25 %wt KOH catalyst and reaction temperature of 44 OC under a molar ratio of methanol and oils of 8:1 and a reaction time of 60 min to achieve the maximum biodiesel yield of 93.56 with the product quality factors satisfying the specification standards which were very close to the experimental values.